TREN HEALTHY FAST FOOD : ANALISIS MODEL BISNIS DAN POTENSI PERTUMBUHAN DI ERA GAYA HIDUP SEHAT DI KOTA MEDAN - Daryana, Aditiya Pratama; Saragih, Vina Gabriella; Akita, Amalia; Girsang, Deddy Ray (UNIKA Santo Thomas, 2025)
The trend of a healthy lifestyle is increasing among urban communities, including in Medan City, driving the growth of the healthy fast food industry. This study aims to analyze the business model and factors influencing the growth of the healthy fast food industry in Medan City using multiple regression analysis. Data were collected through a quantitative survey of 200 healthy food consumers and in-depth interviews with business owners. he findings indicate that digital marketing strategy has the most significant impact on business growth, followed by product pricing and product innovation. Healthy food businesses that optimize marketing through social media, online ordering applications, and digital promotion strategies have a greater opportunity to expand their market share. Meanwhile, although healthy food is relatively more expensive than conventional fast food, consumers are still willing to purchase if the product provides clear health benefits. Product innovation also contributes to increasing customer loyalty. The implications of this study emphasize the importance of digital marketing strategies and innovation in accelerating the growth of healthy food businesses, as well as the need for government policies to support this industry, such as incentives for healthy food entrepreneurs